2016
DOI: 10.1142/s179354581630010x
|View full text |Cite
|
Sign up to set email alerts
|

Structured illumination microscopy and its new developments

Abstract: Optical microscopy allows us to observe the biological structures and processes within living cells. However, the spatial resolution of the optical microscopy is limited to about half of the wavelength by the light di®raction. Structured illumination microscopy (SIM), a type of new emerging super-resolution microscopy, doubles the spatial resolution by illuminating the specimen with a patterned light, and the sample and light source requirements of SIM are not as strict as the other super-resolution microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Previous reports have shown that PI4P-containing vesicles are present at the site of mitochondrial division, but the role played by these vesicles in the highly coordinated steps of mitochondrial division remains unclear. As the morphology of mitochondria, microtubules, microfilaments, and the ER is heterogeneous, with ultrastructural features that are below the diffraction limit, we used SIM [ 22 , 23 , 24 ] to capture the dynamics of subcellular structure better. We found that PI4P-containing vesicles regulate mitochondrial division by changing the content of PI4P derived from Golgi apparatus which is consistent with recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that PI4P-containing vesicles are present at the site of mitochondrial division, but the role played by these vesicles in the highly coordinated steps of mitochondrial division remains unclear. As the morphology of mitochondria, microtubules, microfilaments, and the ER is heterogeneous, with ultrastructural features that are below the diffraction limit, we used SIM [ 22 , 23 , 24 ] to capture the dynamics of subcellular structure better. We found that PI4P-containing vesicles regulate mitochondrial division by changing the content of PI4P derived from Golgi apparatus which is consistent with recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Yang and his colleagues in Fuzhou, China presented two papers in this special issue. In the¯rst paper, 5 they introduced the principle and development of SIM, along with the combination of this technique with other°u orescence imaging techniques. In the second paper, 6 they analyzed the theory of typical polarized lights in the¯eld of focal spot imaging, and used simulated images of°uorescent beads to demonstrate the in°uence of polarized light of di®erent modes on the quality of images of SIM and STED (stimulated emission depletion) microscopy.…”
mentioning
confidence: 99%